Pictorial Essay Penile cancer brachytherapy HDR mould technique used at the Holycross Cancer Center - Matys, Robert; Kubicka-Mendak, Iwona; Łyczek, Jarosław; Pawłowski, Piotr; Stawiarska, Iwona; Miedzinska, Joanna; Banatkiewicz, Paweł; Łaskawska-Wiatr, ldona; Wittych, Justyna (Journal of Contemporary Brachytherapy, 2011)
The aim of this pictorial essay is to present the mould based HDR brachytherapy technique used at the Holycross Cancer Center for penile cancer patients. We use images to describe this method step by step.